A Review: Plant Carbohydrate Types—The Potential Impact on Ruminant Methane Emissions - Sun, Xuezhao; Cheng, Long; Jonker, Arjan; Munidasa, Sineka; Pacheco, David (Frontiers in Veterinary Science, 2022)
Carbohydrates are the major component of most ruminant feeds. The digestion of carbohydrates in the rumen provides energy to the ruminants but also contributes to enteric methane (CH4) emissions. Fresh forage is the main feed for grazing ruminants in temperate regions. Therefore, this review explored how dietary carbohydrate type and digestion affect ruminant CH4 emissions, with a focus on fresh forage grown in temperate regions. Carbohydrates include monosaccharides, disaccharides, oligosaccharides, and polysaccharides. Rhamnose is the only monosaccharide that results in low CH4 emissions. However, rhamnose is a minor component in most plants. Among polysaccharides, pectic polysaccharides lead to greater CH4 production due to the conversion of methyl groups to methanol and finally to CH4. Thus, the degree of methyl esterification of pectic polysaccharides is an important structural characteristic to better understand CH4 emissions. Apart from pectic polysaccharides, the chemical structure of other polysaccharides per se does not seem to affect CH4 formation. However, rumen physiological parameters and fermentation types resulting from digestion in the rumen of polysaccharides differing in the rate and extent of degradation do affect CH4 emissions. For example, low rumen pH resulting from the rapid degradation of readily fermentable carbohydrates decreases and inhibits the activities of methanogens and further reduces CH4 emissions. When a large quantity of starch is supplemented or the rate of starch degradation is low, some starch may escape from the rumen and the escaped starch will not yield CH4. Similar bypass from rumen digestion applies to other polysaccharides and needs to be quantified to facilitate the interpretation of animal experiments in which CH4 emissions are measured. Rumen bypass carbohydrates may occur in ruminants fed fresh forage, especially when the passage rate is high, which could be a result of high feed intake or high water intake. The type of carbohydrates affects the concentration of dissolved hydrogen, which consequently alters fermentation pathways and finally results in differences in CH4 emissions. We recommend that the degree of methyl esterification of pectic polysaccharides is needed for pectin-rich forage. The fermentation type of carbohydrates and rumen bypass carbohydrates should be determined in the assessment of mitigation potential.